20 Years of Indian Gamma Ray Astronomy Using Imaging Cherenkov Telescopes and Road Ahead - Krishna Kumar Singh; Kuldeep Kumar Yadav (Universe, 2021)
The field of ground-based <semantics>γ</semantics>-ray astronomy has made very significant advances over the last three decades with the extremely successful operations of several atmospheric Cherenkov telescopes worldwide. The advent of the imaging Cherenkov technique for indirect detection of cosmic <semantics>γ</semantics> rays has immensely contributed to this field with the discovery of more than 220 <semantics>γ</semantics>-ray sources in the Universe. This has greatly improved our understanding of the various astrophysical processes involved in the non-thermal emission at energies above 100 GeV. In this paper, we summarize the important results achieved by the Indian <semantics>γ</semantics>-ray astronomers from the GeV-TeV observations using imaging Cherenkov telescopes over the last two decades. We mainly emphasize the results obtained from the observations of active galactic nuclei with the TACTIC (TeV Atmospheric Cherenkov Telescope with Imaging Camera) telescope, which has been operational since 1997 at Mount Abu, India. We also discuss the future plans of the Indian <semantics>γ</semantics>-ray astronomy program with special focus on the scientific objectives of the recently installed 21 m diameter MACE (Major Atmospheric Cherenkov Experiment) telescope at Hanle, India.